2023
DOI: 10.1136/bmjgh-2022-010996
|View full text |Cite
|
Sign up to set email alerts
|

How has Guinea learnt from the response to outbreaks? A learning health system analysis

Abstract: IntroductionLearning is a key attribute of a resilient health system and, therefore, is central to health system strengthening. The main objective of this study was to analyse how Guinea’s health system has learnt from the response to outbreaks between 2014 and 2021.MethodsWe used a retrospective longitudinal single embedded case study design, applying the framework conceptualised by Sheikh and Abimbola for analysing learning health systems. Data were collected employing a mixed methods systematic review carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 130 publications
(203 reference statements)
0
0
0
Order By: Relevance
“…Twenty papers included a definition of an LHS [2,31,37,38,40,41,44,46,48,52,54,[57][58][59][60][61][62][63][64][65] (Table 2). Twenty-seven unique references were used to cite these LHS definitions.…”
Section: Lhs Definitions and Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty papers included a definition of an LHS [2,31,37,38,40,41,44,46,48,52,54,[57][58][59][60][61][62][63][64][65] (Table 2). Twenty-seven unique references were used to cite these LHS definitions.…”
Section: Lhs Definitions and Frameworkmentioning
confidence: 99%
“…Of 17 studies (53%) that reported use of an LHS framework, 11 used existing frameworks that were not explicitly modified from their original structure [37,38,40,41,43,46,48,51,56,57,62], 4 adapted an existing framework in response to the COVID-19 pandemic [44,49,59,64], and 2 developed new frameworks [52,54] (Table 2).…”
Section: Lhs Definitions and Frameworkmentioning
confidence: 99%
See 3 more Smart Citations